3D flower-Like Co1−xS/MoS2 composite for long-life and high-rate lithium storage. (February 2020) - Zhu, Kaixun; Zhu, Zhi; Jin, Bo; Li, Huan; Jin, Enmei; Jeong, Sangmun; Jiang, Qing
Highlights: 3D flower-like Co1−xS /MoS2 composite is constructed by a simple two-step hydrothermal reaction. Co1−xS /MoS2 composite displays long-life and high-rate lithium storage. Abstract: Cobalt sulfide (Co1−xS ) and molybdenum disulfide (MoS2 ) are investigated widely as anodes for lithium-ion batteries (LIBs) because of high theoretical capacities and excellent chemical and physical performance. In this study, the unique hexagonal three dimensional (3D) flower-like Co1−xS /MoS2 composite is constructed by a simple two-step hydrothermal reaction with 2-methylimidazole as an adding agent. When applied as an anode for LIBs, Co1−xS /MoS2 composite shows high discharge capacity (1033 mAh g −1 after 100 cycles at 0.2 A g −1 ), good cycling stability (715 mAh g −1 after 500 cycles at 1 A g −1 ), and good rate performance. The good electrochemical performance is put down to the unique hexagonal 3D flower-like structure and the synergistic effect of Co1−xS and MoS2, which not only effectively shortens lithium-ion diffusion pathways but also reduces volume expansion of composite during cycling. The electrochemical testing results manifest that the as-synthesized Co1−xS /MoS2 composite might be a prospective energy storage material for LIBs.